Enhanced Terahertz Sensing via On-Chip Integration of Diffractive Optics with InGaAs Bow-Tie Detectors - Karolis Redeckas; Vytautas Jakštas; Matas Bernatonis; Vincas Tamošiūnas; Gintaras Valušis; Linas Minkevičius (Sensors)
The practical implementation of terahertz (THz) imaging and spectroscopic systems in real operational conditions requires them to be of a compact size, to have enhanced functionality, and to be user-friendly. This work demonstrates the single-sided integration of Fresnel-zone-plate-based optical elements with InGaAs bow-tie diodes directly on a semiconductor chip. Numerical simulations were conducted to optimize the Fresnel zone plate’s focal length and the InP substrate’s thickness to achieve constructive interference at 600 GHz, room-temperature operation and achieve a sensitivity more than an order of magnitude higher—up to 24.5 V/W—than that of a standalone bow-tie detector. Investigations revealed the strong angular dependence of the incident radiation on the Fresnel zone plate-integrated bow-tie diode’s response. These findings pave a promising avenue for the further development of single-sided integration of flat optics with THz detectors, enabling improved sensitivity, simplified manufacturing processes, and reduced costs for THz detection systems in a more compact design scheme.